Brief Report: Clinical Characteristics and Outcomes of Patients With Thoracic SMARCA4-Deficient Undifferentiated Tumors - Alissa J. Cooper, MD; Andrea Arfe, PhD; Biagio Ricciuti, MD; Andréanne Gagné, MD, PhD; Lynette M. Sholl, MD; Alessandro Di Federico, MD; Mark M. Awad, MD, PhD; Mihaela Aldea, MD, PhD; Maria Rosa Ghigna, MD; Miruna Grecea, MD; Phoebe Clark, MS; Jamie E. Chaft, MD; et al. (JTO Clinical and Research Reports)
Introduction: Thoracic SMARCA4-deficient undifferentiated tumors (SMARCA4-UTs) are a recently defined group of aggressive cancers in which the effectiveness of standard treatments for lung cancer is unknown. Methods: We collected clinical, pathologic, and demographic variables from five institutions for patients whose tumors met criteria for SMARCA4-UTs (undifferentiated phenotype and loss of SMARCA4 (BRG1) by immunohistochemistry). Results: We identified 92 patients with SMARCA4-UTs; 58 (63%) had stage IV disease at diagnosis and 16 (17%) developed recurrent or metastatic disease after initial diagnosis. Median overall survival from metastatic diagnosis was 7.3 (95% confidence interval [CI]: 4.6–12.8) months. Of patients with metastatic disease, 58 (78%) received first-line systemic treatment. Most often, patients received chemo and immunotherapy combination (41%), chemotherapy alone (33%), or immunotherapy alone (16%). Median progression-free survival from start of systemic therapy was 1.9 (95% CI: 1.4–14.5) months for chemo and immunotherapy, 1.6 (95% CI: 1.1–5.8) months for chemotherapy, and 3.3 (95% CI: 1.2–undefined) months for immunotherapy alone. Five patients had durable responses (≥2 y); all received immunotherapy as part of first-line regimens. Nine (16%) of 55 tumor samples tested had programmed death-ligand 1 expression more than or equal to 50%, with 24 (44%) negative samples. Tumor mutational burden was available in 48 cases (52%), and median was 10.5 (range: 2–48) mutations per megabase. Conclusions: This multi-institution retrospective cohort analysis revealed a population of patients with short progression-free survival to standard therapies and poor overall survival. A few patients had remarkable response to regimens including immunotherapy. Prospective clinical studies are urgently needed to identify better therapeutic approaches to treat this aggressive malignancy, and this analysis may serve as a benchmark for future clinical trial design.